Aspergillus flavus contamination in two Portuguese wastewater treatment plants - Viegas, Carla (2014)
Filamentous fungi from genus Aspergillus were previously detected in wastewater treatment plants (WWTP) as being Aspergillus flavus (A. flavus), an important toxigenic fungus producing aflatoxins. This study aimed to determine occupational exposure adverse effects due to fungal contamination produced by A. flavus complex in two Portuguese WWTP using conventional and molecular methodologies. Air samples from two WWTP were collected at 1 m height through impaction method. Surface samples were collected by swabbing surfaces of the same indoor sites. After counting A. flavus and identification, detection of aflatoxin production was ensured through inoculation of seven inoculates in coconut-milk agar. Plates were examined under long-wave ultraviolet (UV; 365 nm) illumination to search for the presence of fluorescence in the growing colonies. To apply molecular methods, air samples were also collected using the impinger method. Samples were collected and collection liquid was subsequently used for DNA extraction. Molecular identification of A. flavus was achieved by real-time polymerase chain reaction (RT-PCR) using the Rotor-Gene 6000 qPCR detection system (Corbett). Among the Aspergillus genus, the species that were more abundant in air samples from both WWTP were Aspergillus versicolor (38%), Aspergillus candidus (29.1%), and Aspergillus sydowii (12.7%). However, the most commonly species found on surfaces were A. flavus (47.3%), Aspergillus fumigatus (34.4%), and Aspergillus sydowii (10.8%). Aspergillus flavus isolates that were inoculated in coconut agar medium were not identified as toxigenic strains and were not detected by RT-PCR in any of the analyzed samples from both plants. Data in this study indicate the need for monitoring fungal contamination in this setting. Although toxigenic strains were not detected from A. flavus complex, one cannot disregard the eventual presence and potential toxicity of aflatoxins.